Development of an Analytical Method for the Determination of Trace Lead in Lake Water Samples by Flame Atomic Absorption Spectrophotometry after Vortex Assisted‐Stearic Acid Coated Magnetic Nanoparticle Based Extraction. Issue 2 (13th December 2022) - Serbest, Hakan
Abstract: In the present study, a method is proposed for the determination of lead at trace levels by slotted quartz tube‐flame atomic absorption spectrophotometry (SQT‐FAAS) after preconcentration with stearic acid coated magnetic nanoparticle‐based dispersive solid phase extraction (SA‐MNP‐DSPE). The slotted quartz tube (SQT) is used to enhance the analyte atom residence time in the light path. Stearic acid coated magnetic iron oxide (Fe3 O4 ) nanoparticles, which can be easily collected with an external magnet, are used as adsorbent in the extraction process. The limit of detection (LOD) and the limit of quantitation (LOQ) values of the proposed method are obtained as 0.90 and 2.9 µg L −1, respectively. The method allows high repeatability in a wide linear range between 5.0 and 250 µg L −1, and the relative standard deviation for six replicates is 5.8%. The detection power is enhanced by about 77‐fold compared to the regular flame atomic absorption spectrophotometry (FAAS) system. The method is validated by recovery experiments to four different lake water samples. After the spiking tests, good recovery results are calculated between 97% and 106%. These results show that lead can be detected at low levels in lake water samples with high sensitivity, accuracy, and precision. Abstract : A green analytical method, magnetic nanoparticle‐based dispersive solid phase extraction combined with slotted quartz tube‐flame atomic absorption spectrophotometry, is developed for trace‐level determination of lead (Pb) in lake samples. The magnetic nanoparticles are used as sorbent. The detection power is increased by about 77 times. The recovery results obtained from spiking experiments range between 97% and 106%.